'There is no law that justifies the existence of the board of elders'. Community service and legal pluralism in Santa María, Guatemala. Issue 1 (2nd January 2016) - Rasch, Elisabet Dueholm
ABSTRACT: This article analyzes how indigenous peoples actively engage in the negotiation of international, national and local legal frameworks in Guatemala. The aim of the article is to explain paradoxical outcomes of global legal pluralism through an actor-oriented approach to the construction of legal frameworks and the meaning of rights. It does so by means of a case study of the dissolution of an indigenous social institution: the cargo system. The case study involves a multiplicity of power relations. It is argued that these power relations enable an understanding of the different ways in which local actors engage in processes of constructing legal frameworks 'on the ground'. This article will provide insight into how new legal frameworks constitute social realities. In addition, it will show how personal identifications and experiences are translated into legal practices. Finally, the case study reveals how the struggle for rights both reflects and produces tensions among ethnic, national, social economic and religious identities.